PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR MATEMATIKA - Salisa Safiyana; Dr Junarti; Drs Sujiran (Journal of Technology, Mathematics and Social Science, 2022)
Abstract: The purpose of this study was to determine whether or not there was an effect of the STAD Type Cooperative Learning Model on Learning Outcomes of Primary Mathematics Circles for Class VIII Even Semester SMP Negeri 1 Padangan. The population of this study were all students of SMP Negeri 1 Padangan class VIII. The samples taken were three classes. The data collection technique used is the method used for data collection in this study by using the documentation method, and the test method in the form of multiple choice questions as many as 20 questions. The test instruments used were content validity, item validity, discriminatory power, level of difficulty, and reliability. The prerequisite test used is the normality test using the Lilliefors method and the homogeneity test using the F test. The data analysis technique used is the t test. The results of the calculation in the data analysis show that x = 81.6129 and x = 69.0625, s_1^2 = 132.286 and s_2^2 = 186.189, Fcount = 1.5102 > Ftable = 1.825 (Ho is accepted and the variance is homogeneous), it is obtained tcount = 4.0357 > ttable = 1.999 so Ho is rejected and H1 is accepted. even the 2017/2018 school year.Keywords: STAD; Math Learning Results